A method for purifying groundwater in arsenic-contaminated sites

By combining iron-modified carbon composite material and loaded layered bimetal hydroxide, biochar prepared by hydrogen peroxide and oxygen-spray method, the low efficiency and high cost of groundwater purification in the arsenic-contaminated site in the prior art Problem, efficient and low-cost arsenic pollution treatment has been achieved, especially in treating trivalent arsenic and complex ionic environments, which significantly improves the purification effect.

CN118598329BActive Publication Date: 2025-01-03NANJING INST OF ENVIRONMENTAL SCI MINIST OF ECOLOGY & ENVIRONMENT OF THE PEOPLES REPUBLIC OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410789117.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-19
Publication Date
2025-01-03
Estimated Expiration
2044-06-19

AI Technical Summary

Technical Problem

The existing groundwater purification method for arsenic-contaminated sites is inefficient and costly in treating high concentrations of arsenic and complex ionic environments, especially the removal efficiency of trivalent arsenic (As(III) is insufficient, and the Fenton method reacts under acidic conditions. Restricted, Fe2+ regeneration is difficult and sludge is generated.

Method used

Using iron-modified carbon composite material, the oxidation efficiency of As(III) is improved by adding hydrogen peroxide, and using iron or goiterite to modify biochar and layered bimetal hydroxide material, combined with oxygen-spray The fruit wood biochar prepared by the method improves the adsorption and oxidation capacity of arsenic and is suitable for effectively removing arsenic within a wide pH range.

Benefits of technology

It realizes low-cost and efficient groundwater purification of arsenic-contaminated sites, improves the oxidation and adsorption capacity of trivalent arsenic, reduces the interference of coexisting ions, and is suitable for high-concentration arsenic-contaminated environments in industrial sites, and has stronger material stability and durability. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118598329B_ABST
    Figure CN118598329B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of arsenic pollution remediation, and in particular to a method for purifying groundwater in an arsenic contaminated site, comprising the following steps: S1, adding hydrogen peroxide to groundwater in the arsenic contaminated site with a pH value ranging from 3 to 12, and S2, passing the groundwater in the arsenic contaminated site through an iron-modified carbon composite material at a flow rate of 0.08 to 0.12 mL / min, thereby completing the purification of the groundwater in the arsenic contaminated site; the purification method of the invention considers adding hydrogen peroxide to the system to construct a Fenton-like reaction environment, and using the high adsorption performance of the iron-modified biochar and the good electron transfer performance of the carbon-based material, combined with its strong oxidizing ability, to oxidize highly toxic As(III) to As(V), thereby achieving the effects of efficient detoxification and fixation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of arsenic pollution treatment, and in particular to a method for purifying groundwater in an arsenic-contaminated site. Background Art

[0002] Arsenic pollution is a serious problem at mining and smelting sites. The arsenic pollution in the groundwater of these contaminated sites is characterized by high pollution concentration, uneven distribution, and complex co-existing ions. It has been reported that adsorption materials are mostly used for groundwater contaminated by arsenic of geological high background origin. The adsorption treatment performance of high-concentration arsenic pollution in groundwater of contaminated sites is limited, and it is easily interfered by other high-concentration co-existing ions in the groundwater of the site, resulting in the need for a large amount of adsorption materials and the remediation cost is usually high.

[0003] However, the mobility and toxicity of trivalent arsenic (As(III)) in groundwater are higher than those of pentavalent arsenic (As(V)). How to effectively remove As(III) from the environment has become a major focus of researchers. Among the oxidation methods that use strong oxidizing power to oxidize highly toxic As(III) to As(V), the Fenton method is a widely used method. Its principle is to use high concentrations of H2O2 and Fe 2+ The non-selective strong oxidant ·OH with a high redox potential is produced to oxidize and degrade organic and inorganic pollutants in water. However, this method has certain limitations in practical applications. First, under the acidic conditions required by the traditional Fenton reaction, the neutrally charged H3AsO3 does not react with H2O2, resulting in the reaction being greatly affected by pH. To overcome this problem, it is possible to consider introducing a heterogeneous activator that can react under alkaline conditions to promote the effective reaction of As(III) with H2O2 and improve the oxidation efficiency. Secondly, during the reaction, Fe 2+ The difficulty in regeneration and the generation of a large amount of sludge limit the application of the Fenton process.

[0004] In order to solve the above problems, the present invention decides to design a method for purifying groundwater in arsenic-contaminated sites. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a method for purifying groundwater in an arsenic-contaminated site.

[0006] A method for purifying groundwater in an arsenic-contaminated site comprises the following steps:

[0007] Adding hydrogen peroxide to the groundwater of the arsenic contaminated site, with a molar concentration ratio of hydrogen peroxide / As(III) of 0.003 to 0.03:1;

[0008] The pH value of the groundwater in the arsenic contaminated site is in the range of 3 to 12, and the concentration of As(III) in the groundwater in the arsenic contaminated site is in the range of 1 to 200 mg / L;

[0009] Then, the groundwater from the arsenic contaminated site is passed through the iron-modified carbon composite material at a flow rate of 0.08 to 0.12 mL / min, thereby completing the purification of the groundwater from the arsenic contaminated site;

[0010] Among them, 4 to 9 grams of iron-modified carbon composite material are required to purify 1 liter of groundwater from arsenic-contaminated sites.

[0011] Furthermore, the groundwater in the arsenic contaminated site contains coexisting ions, including SO4 2- 、HCO3 - 、CO3 2- PO4 3- At least one of .

[0012] Note: The above-mentioned coexisting ions usually interfere with the treatment of arsenic pollution. However, under the action of this purification method, the interference of the above-mentioned coexisting ions on the treatment of arsenic pollution is weakened, thereby improving the purification efficiency of groundwater in arsenic-contaminated sites.

[0013] Furthermore, the iron-modified carbon composite material is ferrihydrite-modified biochar, and the preparation method of the ferrihydrite-modified biochar is as follows: dissolve Fe(NO3)3·9H2O in deionized water at a solid-liquid ratio of 1g:12-13mL, then add biochar accounting for 20-30% of the mass of Fe(NO3)3·9H2O, place it on a magnetic stirrer and stir at 250-350rpm for pre-adsorption for 23-25h; then adjust the pH to 7.15-7.25 with 1mol / L KOH solution, and then stir at 350-450rpm for 12-14h; after stirring, centrifuge at 2900-3100rpm to retain the solid, then wash the solid with deionized water, centrifuge it, freeze-dry it, and grind it through a 50-70 mesh nylon sieve to obtain ferrihydrite-modified biochar.

[0014] Description: Under the action of pH, iron ions form iron hydroxide precipitates. Under stirring conditions, iron hydroxide is oxidized to produce ferrihydrite particles. A large number of iron-rich particles are evenly distributed on the surface and pore structure of ferrihydrite-modified biochar. The surface morphology of the iron particles is irregular, and they are distributed in the carbon structure in the form of nanoparticles. Because of their amorphous iron oxide species, they have excellent As adsorption performance and high specific surface area, which is more beneficial to As adsorption.

[0015] Furthermore, the iron-modified carbon composite material is goethite-modified biochar, and the preparation method of the goethite-modified biochar is as follows: the biochar is mixed with a 0.8-1.2 mol / L Fe(NO3)3·9H2O aqueous solution at a solid-liquid ratio of 1 g:9.5-10.5 mL, and then placed in a magnetic stirrer for vigorous stirring at 950-1500 rpm for pre-adsorption for 23-25 ​​hours; then, a 5 mol / L KOH solution is poured while stirring, and the amount of KOH solution added is 1.5-2 times that of the Fe(NO3)3·9H2O aqueous solution; after adding deionized water to make up the volume, it is sealed with tin foil and placed in an oven, and aged at 65-75°C for 50-60 hours; after aging, the solid is retained by centrifugation at 2900-3100 rpm, and the solid is dialyzed in deionized water to a pH of 7-8, and then it is freeze-dried and ground through a 50-70 mesh nylon sieve to obtain goethite-modified biochar.

[0016] Description: Under the action of pH (stronger alkalinity than synthetic ferrihydrite), iron hydroxide precipitate is formed. As the precipitate grows, goethite crystals are obtained. Aging at 70°C for 60 hours promotes the maturity of the crystals and the improvement of crystallinity. The iron particles in goethite-modified biochar are in an elongated needle-like structure and densely distributed on the surface and pores of biochar, which helps to provide more adsorption sites, thereby increasing its adsorption capacity for arsenic. Goethite has a good crystal structure and there are relatively abundant active hydroxyl groups on its surface. These hydroxyl groups can form stable chemical bonds with arsenic, thereby effectively adsorbing arsenic.

[0017] Furthermore, the iron-modified carbon composite material is ferrihydrite-modified carbon loaded with layered double metal hydroxides;

[0018] The preparation method of the ferrihydrite-modified carbon-supported layered double metal hydroxide is as follows:

[0019] S1. Dissolve Fe(NO3)3·9H2O in deionized water at a solid-liquid ratio of 1g:12-13mL, then add biochar accounting for 20-30% of the mass of Fe(NO3)3·9H2O, and stir at 250-350rpm for pre-adsorption for 23-25h; then adjust the pH to 7.15-7.25 with 0.8-1.2mol / L KOH solution, and stir at 350-450rpm for 12-14h; after stirring, centrifuge at 2900-3100rpm to retain the solid, then wash the solid with deionized water, centrifuge, freeze-dry, and grind through a 50-70 mesh sieve to obtain ferrihydrite-modified biochar;

[0020] S2. Add 100 mL of water to 3-5 g of ferrihydrite-modified biochar, stir evenly, add 10 mL of 1 mol / L divalent metal salt, the metal is one of magnesium, nickel, and zinc; place the mixed solution in a reactor, react at 60°C to 80°C for 20h to 24h, centrifuge at 2900-3100 rpm to retain the solid, and wash the solid in deionized water for 3-5 times, then freeze-dry it and grind it through a 50-70 mesh sieve to obtain a composite material of ferrihydrite-modified carbon loaded with layered double metal hydroxides.

[0021] Description: The use of iron-modified biochar loaded with layered double hydroxides can, on the one hand, utilize the positively charged properties of the layered double hydroxides to neutralize the negative charge of the biochar, making the anionic arsenic more accessible to the composite material; on the other hand, the anion exchange properties of the layered double hydroxides can be used to further improve the removal efficiency of arsenic in groundwater.

[0022] Furthermore, the iron-modified carbon composite material is goethite-modified biochar loaded with layered double metal hydroxides.

[0023] The preparation method of the goethite-modified carbon-supported layered double metal hydroxide is as follows:

[0024] S1', mix the biochar with a 0.8-1.2 mol / L Fe(NO3)3·9H2O aqueous solution at a solid-liquid ratio of 1 g: 9.5-10.5 mL, and then stir vigorously at 950-1500 rpm for pre-adsorption for 23-25 ​​hours; then pour in a 4.8-5.2 mol / L KOH solution while stirring, and the amount of KOH solution added is 1.5-2 times that of the Fe(NO3)3·9H2O aqueous solution; then add deionized water to make up the volume, seal it with tin foil and put it in an oven, and age it at 65-75°C for 50-60 hours; after aging, centrifuge at 2900-3100 rpm to retain the solid, and dialyze the solid in deionized water to a pH of 7-8, then freeze-dry it and grind it through a 50-70 mesh sieve to obtain goethite-modified biochar;

[0025] S2', add 100mL of water to 3-5g of goethite-modified biochar, stir evenly, add 10mL of 1mol / L divalent metal salt, the metal is one of magnesium, nickel and zinc; put the mixed solution into a reactor, react at 60℃~80℃ for 20h~24h, centrifuge at 2900~3100rpm to retain the solid, and wash the solid in deionized water for 3-5 times, then freeze-dry it and grind it through a 50-70 mesh sieve to obtain a composite material of goethite-modified carbon loaded with layered double metal hydroxide.

[0026] Description: The use of iron-modified biochar loaded with layered double hydroxides can, on the one hand, utilize the positively charged properties of the layered double hydroxides to neutralize the negative charge of the biochar, making the anionic arsenic more accessible to the composite material; on the other hand, the anion exchange properties of the layered double hydroxides can be used to further improve the removal efficiency of arsenic in groundwater.

[0027] Furthermore, in the iron-modified carbon composite material, the biochar is fruit wood biochar prepared by an oxygen exposure-spraying method, and is dried and ground through a 50-70 mesh nylon sieve for standby use before use.

[0028] Description: Through oxygenation and spraying processes, the specific surface area and porosity of pear wood biochar can be increased, thereby enhancing its adsorption capacity for arsenic. Pear wood biochar itself contains rich organic matter and minerals, which can form stable complexes with arsenic, reducing the mobility and bioavailability of arsenic in groundwater.

[0029] Furthermore, the preparation method of the fruit tree biochar is as follows: solid alcohol is used as an igniter to ignite the precursor agricultural waste fruit tree branches, and oxygen is supplemented by the self-heating pressure difference generated by the combustion until the branches burn to black and red, and water is sprayed on the fruit tree branches in a spraying manner, and the water spraying volume is 50L / m 3 After the carbonized branches stop burning and cool down, the precursor is used to obtain fruit wood biochar.

[0030] Compared with the existing arsenic-contaminated groundwater purification method, the present invention has the following beneficial effects:

[0031] (1) The iron-modified carbon composite material used in the arsenic purification method designed by the present invention is low-cost and has a high-efficiency oxidation-adsorption capacity for arsenic; and the present invention further improves the oxidation-adsorption capacity of the material for arsenic by constructing a Fenton-like system (i.e., the addition of hydrogen peroxide), and the introduction of hydrogen peroxide promotes the efficiency of the iron-modified carbon composite material in converting As(III) into As(V), thereby converting more highly toxic trivalent arsenic into less toxic pentavalent arsenic in a short period of time, thereby improving the detoxification effect; in addition, the purification method of the present invention still has ultra-high adsorption and removal performance for contaminated groundwater with high-concentration arsenic pollution in industrial sites and coexistence of complex background ions, and has a wide range of applications.

[0032] (2) The iron-modified biochar loaded with layered double metal hydroxides used in the arsenic purification method designed by the present invention can, on the one hand, utilize the positively charged nature of the layered double metal hydroxide to neutralize the negative charge of the biochar, making the anionic arsenic more accessible to the composite material, and on the other hand, utilize the anion exchange performance of the layered double metal hydroxide to further improve the removal efficiency of arsenic in groundwater. In addition, the overall stability and durability of the loaded material are stronger, and the impact of the environment is smaller, so that the modified biochar has a longer life and better stability during use. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The kinetic adsorption and isothermal adsorption diagrams of As(III) by FhGM, GtGM, FhGM-H2O2 and GtGM-H2O2 of the present invention are shown;

[0034] Figure 2 This is a diagram showing the effect of the coexisting ions on the As(III) removal rate of the present invention;

[0035] Figure 3 This is a diagram showing the effect of different pH values ​​on As(III) adsorption and oxidation removal in the present invention;

[0036] Figure 4 This is a graph showing the experimental results of the adsorption-oxidation removal of groundwater from arsenic-contaminated sites by a column filled with 1% by mass of FhGM or GtGM of the present invention. DETAILED DESCRIPTION

[0037] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0038] Example 1: A method for purifying groundwater in an arsenic-contaminated site, comprising the following steps:

[0039] Add hydrogen peroxide solution to the groundwater of the arsenic contaminated site, with a molar concentration ratio of hydrogen peroxide / As(III) of 0.015:1;

[0040] The groundwater in the arsenic contaminated site comes from the contaminated groundwater of a retired sulfuric acid production enterprise. The pH value of the groundwater in the arsenic contaminated site is 6, the concentration of As(III) in the groundwater in the arsenic contaminated site is 50 mg / L, and the groundwater in the arsenic contaminated site contains coexisting ions, including 4240 mg / L of SO4 2- , 1980mg / L HCO3 - , 2430mg / L CO3 2- ;

[0041] Then, the groundwater from the arsenic-contaminated site is passed through the iron-modified carbon composite material at a flow rate of 0.1 mL / min, thereby completing the purification of the groundwater from the arsenic-contaminated site;

[0042] Among them, 6.5g of iron-modified carbon composite material is required to purify 1L of groundwater from arsenic-contaminated sites;

[0043] The iron-modified carbon composite material is ferrihydrite-modified biochar, wherein the biochar is pear wood biochar prepared by an oxygen exposure-spraying method, and is dried and ground through a 60-mesh sieve for standby use before use;

[0044] The preparation method of pear wood biochar is as follows: solid alcohol is used as an igniter to ignite the precursor agricultural waste pear tree branches, and the self-heating pressure difference generated by the combustion is used to supplement oxygen until the pear tree branches burn to black and red, and then water is sprayed on the pear tree branches in a spraying manner, and the water spraying volume is 50L / m 3 After the pear tree branches stop burning and cool down, pear wood biochar is obtained;

[0045] The preparation method of the ferrihydrite-modified biochar is as follows: Fe(NO3)3·9H2O is dissolved in deionized water at a solid-liquid ratio of 1g:12.5mL, and then biochar accounting for 25% of the mass of Fe(NO3)3·9H2O is added, and pre-adsorbed at 300rpm for 24h; then the pH is adjusted to 7.2 with a 1mol / L KOH solution, and then stirred at 400rpm for 13h; after the stirring is completed, the solid is retained after centrifugation at 3000rpm, and then the solid is washed with deionized water, centrifuged, freeze-dried, and ground through a 60-mesh sieve to obtain ferrihydrite-modified biochar, i.e., FhGM.

[0046] Example 2: This example is different from Example 1 in that the concentration of As(III) in the groundwater of the arsenic contaminated site is 1 mg / L, and the molar concentration ratio of hydrogen peroxide / As(III) is 0.03:1.

[0047] Example 3: This example is different from Example 1 in that the concentration of As(III) in the groundwater of the arsenic contaminated site is 200 mg / L, and the molar concentration ratio of hydrogen peroxide / As(III) is 0.003:1.

[0048] Example 4: This example is different from Example 1 in that the groundwater from the arsenic-contaminated site is passed through the iron-modified carbon composite material at a flow rate of 0.08 mL / min.

[0049] Example 5: This example is different from Example 1 in that the groundwater from the arsenic-contaminated site is passed through the iron-modified carbon composite material at a flow rate of 0.12 mL / min.

[0050] Example 6: This example is different from Example 1 in that 4 g of iron-modified carbon composite material is required to purify 1 L of groundwater from an arsenic-contaminated site.

[0051] Example 7: This example is different from Example 1 in that 9 g of iron-modified carbon composite material is required to purify 1 L of groundwater in an arsenic-contaminated site.

[0052] Example 8: The difference between this example and Example 1 is that Fe(NO3)3·9H2O is dissolved in deionized water at a solid-liquid ratio of 1 g:13 mL, and then biochar accounting for 20% of the mass of Fe(NO3)3·9H2O is added, and pre-adsorption is carried out by stirring at 250 rpm for 23 hours.

[0053] Example 9: The difference between this example and Example 1 is that Fe(NO3)3·9H2O is dissolved in deionized water at a solid-liquid ratio of 1 g:12 mL, and then biochar accounting for 30% of the mass of Fe(NO3)3·9H2O is added, and pre-adsorption is carried out by stirring at 350 rpm for 25 hours.

[0054] Example 10: This example is different from Example 1 in that the pH is adjusted to 7.25 with 0.8 mol / L KOH solution, and then stirred at 350 rpm for 12 h.

[0055] Example 11: This example is different from Example 1 in that the pH is adjusted to 7.15 with 1.2 mol / L KOH solution, and then stirred at 450 rpm for 14 h.

[0056] Example 12: This example is different from Example 1 in that the solid is retained after centrifugation at 2900 rpm, and then the solid is washed with deionized water, freeze-dried after centrifugation, and ground through a 50-mesh sieve.

[0057] Example 13: This example is different from Example 1 in that the solid is retained after centrifugation at 3100 rpm, and then the solid is washed with deionized water, freeze-dried after centrifugation, and ground through a 70-mesh sieve.

[0058] Example 14: The difference between this example and Example 1 is that the iron-modified carbon composite material is goethite-modified biochar, and the preparation method of the goethite-modified biochar is as follows: mix the biochar with a 1 mol / L Fe(NO3)3·9H2O aqueous solution at a solid-liquid ratio of 1 g:10 mL, and then vigorously stir at 1000 rpm for pre-adsorption for 24 hours; then pour 5 mol / L KOH solution while stirring, and the amount of KOH solution added is 1.8 times that of the Fe(NO3)3·9H2O aqueous solution; after adding deionized water to make up the volume, seal it with tin foil and put it into an oven, and age it at 70°C for 55 hours; after aging, centrifuge at 3000 rpm to retain the solid, and dialyze the solid in deionized water to a pH of 7-8, then freeze-dry it and grind it through a 60-mesh sieve to obtain goethite-modified biochar, i.e., GtGM.

[0059] Example 15: This example differs from Example 14 in that the biochar is mixed with a 0.8 mol / L Fe(NO3)3·9H2O aqueous solution at a solid-liquid ratio of 1 g:9.5 mL, and then pre-adsorbed for 23 h with vigorous stirring at 950 rpm.

[0060] Example 16: This example is different from Example 14 in that the biochar is mixed with a 1.2 mol / L Fe(NO3)3·9H2O aqueous solution at a solid-liquid ratio of 1 g:10.5 mL, and then pre-adsorbed for 25 h with vigorous stirring at 1500 rpm.

[0061] Example 17: This example is different from Example 14 in that 4.8 mol / L KOH solution is poured into the solution while stirring, and the amount of KOH solution added is 1.5 times that of the Fe(NO3)3·9H2O aqueous solution.

[0062] Example 18: This example differs from Example 14 in that 5.2 mol / L KOH solution is poured in while stirring, and the amount of KOH solution added is twice that of the Fe(NO3)3·9H2O aqueous solution.

[0063] Example 19: This example is different from Example 14 in that the aging is performed at 65°C for 50 hours.

[0064] Example 20: This example is different from Example 14 in that the aging is performed at 75°C for 60 hours.

[0065] Example 21: This example is different from Example 14 in that the solid is dialyzed in deionized water until the pH is 7.

[0066] Example 22: This example is different from Example 14 in that the solid is dialyzed in deionized water until the pH is 8.

[0067] Example 23: This example is different from Example 1 in that the iron-modified carbon composite material is ferrihydrite-modified carbon loaded with layered double metal hydroxide;

[0068] The preparation method of the ferrihydrite-modified carbon-supported layered double metal hydroxide is as follows:

[0069] S1. Dissolve Fe(NO3)3·9H2O in deionized water at a solid-liquid ratio of 1g:12.5mL, then add biochar accounting for 25% of the mass of Fe(NO3)3·9H2O, and stir at 300rpm for pre-adsorption for 24h; then adjust the pH to 7.2 with 1mol / L KOH solution, and stir at 400rpm for 13h; after stirring, centrifuge at 3000rpm and retain the solid, then wash the solid with deionized water, centrifuge, freeze-dry, and grind through a 60-mesh sieve to obtain ferrihydrite-modified biochar;

[0070] S2. Add 100 mL of water to 4 g of ferrihydrite-modified biochar, stir evenly, add 10 mL of 1 mol / L magnesium chloride, stir evenly; place the mixed solution in a reactor, react at 70 ° C for 22 hours, centrifuge at 3000 rpm to retain the solid, and wash the solid in deionized water for 4 times, then freeze-dry it and grind it through a 60-mesh sieve to obtain a composite material of ferrihydrite-modified carbon loaded with layered double metal hydroxides.

[0071] Example 24: The difference between this example and Example 23 is that Fe(NO3)3·9H2O is dissolved in deionized water at a solid-liquid ratio of 1 g:13 mL, and then biochar accounting for 20% of the mass of Fe(NO3)3·9H2O is added, and pre-adsorption is carried out by stirring at 250 rpm for 23 hours.

[0072] Example 25: The difference between this example and Example 23 is that Fe(NO3)3·9H2O is dissolved in deionized water at a solid-liquid ratio of 1 g:12 mL, and then biochar accounting for 30% of the mass of Fe(NO3)3·9H2O is added, and pre-adsorption is carried out by stirring at 350 rpm for 25 hours.

[0073] Example 26: This example differs from Example 23 in that the pH is adjusted to 7.25 with 0.8 mol / L KOH solution, and then stirred at 350 rpm for 12 h.

[0074] Example 27: This example differs from Example 23 in that the pH is adjusted to 7.15 with 1.2 mol / L KOH solution, and then stirred at 450 rpm for 14 h.

[0075] Example 28: This example differs from Example 23 in that the solid is retained after centrifugation at 2900 rpm, and then the solid is washed with deionized water, freeze-dried after centrifugation, and ground through a 50-mesh sieve.

[0076] Example 29: This example is different from Example 23 in that the solid is retained after centrifugation at 3100 rpm, and then the solid is washed with deionized water, freeze-dried after centrifugation, and ground through a 70-mesh sieve.

[0077] Example 30: This example is different from Example 23 in that 100 mL of water is added to 3 g of ferrihydrite-modified biochar, and 10 mL of 1 mol / L zinc nitrate is added.

[0078] Example 31: This example is different from Example 23 in that 100 mL of water is added to 5 g of ferrihydrite-modified biochar, and 10 mL of 1 mol / L nickel octanoate is added.

[0079] Example 32: This example is different from Example 23 in that the mixed solution is placed in a reactor, reacted at 60°C for 20 hours, centrifuged at 2900 rpm to retain the solid, and the solid is washed three times in deionized water, then freeze-dried and ground through a 50-mesh sieve.

[0080] Example 33: The difference between this example and Example 23 is that the mixed solution is placed in a reactor, reacted at 80°C for 24 hours, centrifuged at 3100 rpm to retain the solid, and the solid is placed in deionized water for washing 5 times, then freeze-dried and ground through a 70-mesh sieve.

[0081] Example 34: This example is different from Example 1 in that the iron-modified carbon composite material is goethite-modified biochar loaded with layered double metal hydroxides.

[0082] The preparation method of the goethite-modified carbon-supported layered double metal hydroxide is as follows:

[0083] S1', mix the biochar with a 1 mol / L Fe(NO3)3·9H2O aqueous solution at a solid-liquid ratio of 1 g:10 mL, and then stir vigorously at 1000 rpm for pre-adsorption for 24 hours; then pour in a 5 mol / L KOH solution while stirring, and the amount of KOH solution added is 1.8 times that of the Fe(NO3)3·9H2O aqueous solution; then add deionized water to make up the volume, seal it with tin foil and put it in an oven, and age it at 70°C for 55 hours; after aging, centrifuge at 3000 rpm to retain the solid, and dialyze the solid in deionized water to a pH of 7.5, then freeze-dry it and grind it through a 60-mesh sieve to obtain goethite-modified biochar;

[0084] S2', add 100mL of water to 4g of goethite-modified biochar, stir evenly, add 10mL of 1mol / L magnesium chloride, stir evenly; place the mixed solution in a reactor, react at 70°C for 22h, centrifuge at 3000rpm to retain the solid, and wash the solid in deionized water 4 times, then freeze-dry it and grind it through a 60-mesh sieve to obtain a composite material of goethite-modified carbon loaded with layered double metal hydroxide.

[0085] Example 35: This example differs from Example 34 in that the biochar is mixed with a 0.8 mol / L Fe(NO3)3·9H2O aqueous solution at a solid-liquid ratio of 1 g:9.5 mL, and then pre-adsorbed at 950 rpm with vigorous stirring for 23 h.

[0086] Example 36: This example differs from Example 34 in that the biochar is mixed with a 1.2 mol / L Fe(NO3)3·9H2O aqueous solution at a solid-liquid ratio of 1 g:10.5 mL, and then pre-adsorbed for 25 h with vigorous stirring at 1500 rpm.

[0087] Example 37: This example differs from Example 34 in that 4.8 mol / L KOH solution is poured in while stirring, and the amount of KOH solution added is 1.5 times that of the Fe(NO3)3·9H2O aqueous solution.

[0088] Example 38: This example differs from Example 34 in that 5.2 mol / L KOH solution is poured in while stirring, and the amount of KOH solution added is twice that of the Fe(NO3)3·9H2O aqueous solution.

[0089] Example 39: This example differs from Example 34 in that the aging is performed at 65°C for 50 h.

[0090] Example 40: This example is different from Example 34 in that the aging is carried out at 75°C for 60 hours.

[0091] Example 41: This example is different from Example 34 in that the solid is dialyzed in deionized water until the pH is 7.

[0092] Example 42: This example is different from Example 34 in that the solid is dialyzed in deionized water until the pH is 8.

[0093] Example 43: This example is different from Example 34 in that 100 mL of water is added to 3 g of ferrihydrite-modified biochar, and 10 mL of 1 mol / L zinc nitrate is added.

[0094] Example 44: This example is different from Example 34 in that 100 mL of water is added to 5 g of ferrihydrite-modified biochar, and 10 mL of 1 mol / L nickel octanoate is added.

[0095] Example 45: This example is different from Example 34 in that the mixed solution is placed in a reactor, reacted at 60°C for 20 hours, centrifuged at 2900 rpm to retain the solid, and the solid is washed three times in deionized water, then freeze-dried and ground through a 50-mesh sieve.

[0096] Example 46: This example is different from Example 34 in that the mixed solution is placed in a reactor, reacted at 80°C for 24 hours, centrifuged at 3100 rpm to retain the solid, and the solid is washed 5 times in deionized water, then freeze-dried and ground through a 70-mesh sieve.

[0097] Experimental Example: The description of this experimental example is based on the scheme described in Example 1, and is intended to illustrate the practical application effect of the present invention.

[0098] 1. To investigate the adsorption of As(III) by FhGM or GtGM in groundwater of arsenic contaminated sites.

[0099] Solution batch experiments were conducted in 15 mL polypropylene centrifuge tubes. A certain mass of material was weighed into a centrifuge tube, and the solid-liquid ratio was unified as 1 g / L according to the preliminary experimental results. In the kinetic adsorption experiment, 10 mg / L of As(Ⅲ) adsorption solution and 10 mg FhGM or GtGM were added to a 15 mL centrifuge tube, placed in a constant temperature oscillating box and oscillated at 26°C and 180 rpm. Samples were taken out at specific intervals, filtered with a 0.45 μm polyethersulfone filter membrane, and the supernatant was saved for testing. In the isothermal adsorption experiment, As(Ⅲ) or As(Ⅴ) adsorption solutions with different initial concentrations were added, oscillated for 48 hours until the reaction equilibrium, and filtered and saved for testing. The total arsenic residual in the filtrate was determined by inductively coupled plasma mass spectrometry, and As(Ⅲ) was determined by atomic fluorescence spectrometry.

[0100] The case results show that FhGM and GtGM have a fast adsorption rate for As(III), reaching equilibrium in about 6 hours ( Figure 1 a), and their maximum adsorption capacities were 45.76 mg / g and 20.22 mg / g respectively ( Figure 1 b). It is noteworthy that FhGM exhibits superior As adsorption performance, which is attributed to its amorphous iron oxide species, which have stronger As adsorption capacity than the crystalline iron oxides in GtGM. In addition, FhGM has a higher specific surface area (153.8 m 2 / g), compared with GtGM (77.5m 2 / g), which is more beneficial to As adsorption.

[0101] Table 1 Effect of the preparation parameters of FhGM or GtGM in Examples 1, 8 to 22 on the adsorption rate of As(III) by FhGM or GtGM in groundwater of arsenic contaminated sites 5 min before the experiment

[0102]

[0103]

[0104] From the results in Table 1, it can be seen that by comparing Examples 1 and 8 to 13, too small or too large mixing parameters of biochar, too small or too large adjustment parameters of KOH, and too large centrifugal grinding parameters will reduce the adsorption rate of FhGM. In Example 13, the adsorption rate is improved, but the improvement is too small. Therefore, the FhGM preparation parameters of Example 1 are relatively better; by comparing Examples 14 to 22, it can be seen that too small or too large mixing parameters of biochar, too small or too large adjustment parameters of KOH, too small aging parameters, and too small or too large dialysis parameters will reduce the adsorption rate of GtGM. In Example 20, the aging parameter is larger but the improvement is consistent with that of Example 14. From an economic point of view, the effect of Example 14 is relatively better; by comparing Examples 1 and 14, it can be seen that the FhGM preparation parameters of Example 1 are relatively better.

[0105] 2. Investigate the adsorption-oxidation experiment of FhGM-H2O2 or GtGM-H2O2 on As(Ⅲ) in groundwater of arsenic contaminated sites.

[0106] First, add As(Ⅲ) adsorption liquid to the centrifuge tube containing the adsorbent, and then add a certain concentration of hydrogen peroxide solution. This heterogeneous Fenton mode of pre-adsorption with the addition of H2O2 later is more conducive to the removal of pollutants than the pre-mixing mode of adding H2O2 first. After the solid and liquid are mixed, the mixed solution is placed in a constant temperature oscillating box, the temperature is set to 26°C, and the oscillation rate is 180rpm. Take out the sample at each kinetic time point, filter it with a 0.45μm polyethersulfone filter membrane, and measure it as soon as possible. In the isothermal adsorption experiment, different initial concentrations of As(Ⅲ) are added, shaken for 48 hours to reach reaction equilibrium, and then filtered and stored for testing. The total arsenic residual in the filtrate is determined by inductively coupled plasma mass spectrometry, and As(Ⅲ) is determined by atomic fluorescence spectrometry.

[0107] When H2O2 was added, the concentration of As(III) decreased rapidly, e.g. Figure 1 c and Figure 1d. Within the first 5 minutes, As(III) in water decreased significantly to 4 mg / L and 2 mg / L in the FhGM and FhGM-H2O2 scenarios. Correspondingly, the concentration of As(V) in water initially increased to a maximum of 7.5 μg / L and 15 μg / L, and then decreased to a lower detection limit within 60 min. Similar trends in As(III) concentration were observed in the GtGM and GtGM-H2O2 scenarios, where As(III) in water decreased significantly to 5.1 mg / L and 3.2 mg / L within the first 5 minutes. It is noteworthy that As(V) concentrations remained at higher levels of 50 μg / L and 1.2 mg / L in the GtGM and GtGM-H2O2 scenarios, respectively. This is due to the relatively lower adsorption capacity of As(V) by GtGM compared to FhGM. These results indicate that the addition of H2O2 is beneficial to the detoxification of As(III), regardless of whether As(V) is adsorbed on FhGM or partially remains in the solution in the GtGM scenario.

[0108] Table 2 Effect of parameters in Examples 1 to 7 on the adsorption-oxidation rate of As(III) in groundwater of arsenic contaminated sites by FhGM-H2O2 5 min before the experiment

[0109]

[0110] It can be seen from the results in Table 2 that too small a proportion of hydrogen peroxide concentration, too small or too large a groundwater flow rate, and too small or too large a proportion of FhGM will reduce the adsorption-oxidation rate of As(III) in groundwater of arsenic contaminated sites. In Example 2, the proportion of hydrogen peroxide concentration is too high, which increases the adsorption-oxidation rate of As(III), but the increase in the rate is greater with the amount of hydrogen peroxide added. Therefore, from an economic point of view, the parameter effect of Example 1 is better.

[0111] 3. Explore the anti-interference test of FhGM and GtGM on coexisting ions in groundwater of arsenic contaminated sites.

[0112] In order to explore the effect of coexisting ions in groundwater on As(Ⅲ) removal, different concentrations of SO4 2- 、HCO3 - 、CO3 2- PO4 3- Effect on As(Ⅲ) removal efficiency, where C0(H2O2)=1mmol / L, C0(As(Ⅲ))=133.4mmol / L(1mg / L), pH of groundwater in arsenic contaminated site=6; the results are as follows Figure 2 As shown, in the FhGM and GtGM treatments, when PO4 3- When the concentration was 10 mg / L, the removal efficiency of As(Ⅲ) was inhibited to a certain extent, and after adding H2O2, the influence of coexisting ions was further reduced.

[0113] 4. Explore the wide pH range in which iron-modified biochar materials can be used to remove trivalent arsenic.

[0114] In order to explore the effect of groundwater with different pH ranges on As(III) removal, the removal of As(III) from aqueous solution by this material was also investigated in the pH range of 3 to 12. The results are as follows Figure 3 As shown. It can be found that in the FhGM-H2O2 treatment, within the pH range of 3 to 9, trivalent arsenic is oxidized to pentavalent arsenic and adsorbed onto the material (as shown by the final residual concentration of total arsenic close to 0), indicating that the FhGM-H2O2 system reduces the total amount of arsenic in groundwater within a relatively wide pH range. In the GtGM-H2O2 treatment, within the pH range of 4 to 9, most of the trivalent arsenic is adsorbed after being oxidized to pentavalent arsenic, and a small part remains in the solution, indicating that the GtGM-H2O2 system converts the more toxic trivalent arsenic into the less toxic pentavalent arsenic within a relatively wide pH range, achieving a detoxification effect.

[0115] 5. Use a column adsorption-oxidation device to explore the effect of purification method parameters on the purification effect of groundwater in arsenic contaminated sites.

[0116] Glass chromatography column: equipped with a polytetrafluoroethylene head and valve, column length 7.0 cm, diameter 2.0 cm;

[0117] Lining at both ends of the column: 500 mesh nylon screen;

[0118] Control column: filled with pure quartz sand only;

[0119] Quartz sand pretreatment: Use 0.1mol / L HCl to remove surface impurities, then rinse thoroughly with deionized water and air dry;

[0120] Filling material: quartz sand (20-40 mesh sieve) and 1% by mass of iron-modified carbon composite material are uniformly mixed.

[0121] Example 1: A peristaltic pump was used to inject groundwater from an arsenic-contaminated site with hydrogen peroxide solution into a packed column from the water inlet at the bottom of the column at a rate of 0.1 mL / min. A partial collector was used to collect samples at regular intervals to analyze the total arsenic and trivalent arsenic concentrations.

[0122] Figure 4 In a, the initial concentration of As(III) C0 = 70 μg / L, and no H2O2 and iron-modified carbon composites were applied; Figure 4 In b, the initial concentration of As(III) C0 = 50 mg / L, the enhanced effect of adsorption-oxidation removal of groundwater from arsenic contaminated sites after mixing with 1 mmol / L H2O2, without applying H2O2 and iron-modified carbon composites; Figure 4In c, the initial concentration of As(III) C0 = 200 mg / L, the column was filled with 1% FhGM, and no H2O2 was applied; Figure 4 In d, the initial concentration of As(III) C0 = 50 mg / L, the column was filled with 1% GtGM, and H2O2 was not applied;

[0123] from Figure 4 It can be seen that after 3.5 pore volumes (PV), the effluent total As (As(tot)) concentration remained consistent with the influent concentration. However, no As(tot) was detected in the effluent of Example 1 during the entire experimental period (27 PVs in total, 20 PVs shown), which confirms the excellent ability of FhGM in treating actual arsenic-contaminated groundwater.

[0124] like Figure 4 As shown in (b), the effluent As(tot) concentration in the FhGM system reached a maximum of about 2 μg / L, which is lower than the Class III standard (10 μg / L) in the Groundwater Quality Standard (GB14848-2017). After flushing with deionized water, the effluent As(tot) concentration did not change significantly. However, in the GtGM system, the effluent As(tot) concentration increased to 61.2 μg / L after 2.4 PV and further increased to 14 mg / L after 5.1 PV. Even after additional continuous flushing with deionized water for 10 PVs, the effluent As(tot) remained at 1.6 mg / L. These results indicate that FhGM exhibits excellent in situ arsenic adsorption and fixation capabilities.

[0125] like Figure 4 c and Figure 4As shown in Figure d, after 2.6 PVs (66.3 mL), the effluent As(tot) concentration began to exceed 10 μg / L and reached 55 mg / L after 4.5 PVs. Deionized water was then introduced, and after 7 PVs of flushing, the effluent As(tot) concentration stabilized at 4.5 mg / L. During the entire experiment, As(III) was mainly present in FhGM, indicating that As(V) was more easily fixed and less easily released in FhGM. For GtGM, an arsenic concentration of 50 mg / L was maintained in the adsorption-oxidation experiment, and the effluent As(tot) concentration always exceeded 10 μg / L during the entire experiment, reaching 1.6 mg / L after 9 PVs. After 6 PVs of flushing with deionized water, the effluent As(tot) concentration remained at 0.4 mg / L. In the effluent liquid, a larger proportion of As(V) was detected in GtGM after 7 PVs. Considering that iron minerals can more easily fix As(V) than As(III), this result suggests that most of As(III) was oxidized to As(V) at an initial concentration of 50 mg / L. This result suggests that most of As(III) was oxidized to As(V) at an initial concentration of 50 mg / L. In addition, the introduction of H2O2 promoted the conversion of As(III) to As(V) by GtGM, compared with the results without the addition of H2O2, thus further enhancing the arsenic attenuation and fixation performance.

[0126] 6. To investigate the effect of the preparation parameters of ferrihydrite-modified biochar loaded with layered double hydroxides / goethite-modified biochar loaded with layered double hydroxides on the purification efficiency of groundwater in arsenic-contaminated sites.

[0127] Table 3 Effect of ferrihydrate-modified biochar loaded with layered double hydroxides on the adsorption rate of As(III) in groundwater from arsenic contaminated sites in Examples 23 to 33

[0128]

[0129] Table 4 Effect of goethite-modified biochar loaded with layered double hydroxides on the adsorption-oxidation rate of As(III) in groundwater from arsenic-contaminated sites in Examples 34-46

[0130]

[0131]

[0132] From the results in Tables 1 to 4, it can be seen that the effect of ferrihydrite-modified biochar loaded with layered double metal hydroxides / goethite-modified biochar loaded with layered double metal hydroxides is significantly improved compared with the FhGM of Example 1;

[0133] By comparing Examples 23 to 33, it can be seen that the effects of the preparation parameters of FhGM on the ferrihydrite-modified biochar loaded with layered double hydroxides are similar to those on FhGM itself, and the ratio of ferrihydrite-modified biochar to divalent metal salt is too small or too large, and the reaction centrifugation of the mixed solution is too small, which will reduce the improvement of the adsorption-oxidation rate of As(III) in groundwater of arsenic contaminated sites. The reaction centrifugation and other parameters of the mixed solution in Example 33 are greater, which further improves the improvement, but compared with the improvement of parameters, the economic effect is not high. Therefore, from the perspective of economy, the effect of Example 23 is relatively better.

[0134] By comparing Examples 34 to 46, it can be seen that the effects of the preparation parameters of GtGM on the ferrihydrite-modified biochar loaded with layered double hydroxides are similar to those on GtGM itself, while the ratio of goethite-modified biochar to divalent metal salt is too small or too large, and the reaction centrifugation of the mixed solution is too small, which will reduce the improvement of the adsorption-oxidation rate of As(III) in groundwater of arsenic contaminated sites. The reaction centrifugation and other parameters of the mixed solution in Example 46 are greater, which further improves the improvement, but compared with the improvement of parameters, the economic effect is not high. Therefore, from the perspective of economy, the effect of Example 34 is relatively better.

[0135] And by comparing the results in Table 3 and Table 4, it can be seen that since FhGM is better than GtGM, it is also applicable to ferrihydrite-modified biochar loaded with layered double metal hydroxides and goethite-modified biochar loaded with layered double metal hydroxides, that is, ferrihydrite-modified biochar loaded with layered double metal hydroxides has a better effect.

[0136] In summary, FhGM-H2O2 has a better effect on the adsorption-oxidation rate of As(III) in groundwater of arsenic contaminated sites, and can also efficiently treat As(III) under the influence of coexisting ions. Ferrihydrite-modified biochar loaded with layered double hydroxides combines the advantages of ferrihydrite-modified biochar and layered double hydroxides. Compared with FhGM, ferrihydrite-modified biochar loaded with layered double hydroxides further increases the adsorption rate of As(III) in groundwater of arsenic contaminated sites. Compared with FhGM-H2O2, ferrihydrite-modified biochar loaded with layered double hydroxides-H2O2 also further increases the adsorption-oxidation rate of As(III) in groundwater of arsenic contaminated sites.

Claims

1. A method for purifying groundwater in an arsenic-contaminated site, characterized in that: The following steps are involved: Add hydrogen peroxide solution to the groundwater of the arsenic contaminated site, with a molar concentration ratio of hydrogen peroxide / As(III) of 0.003~0.03:1; The pH value of the groundwater in the arsenic contaminated site ranges from 3 to 12, and the concentration of As(III) in the groundwater in the arsenic contaminated site ranges from 1 to 200 mg / L. Then, the groundwater from the arsenic-contaminated site is passed through the iron-modified carbon composite material at a flow rate of 0.08-0.12 mL / min, thereby completing the purification of the groundwater from the arsenic-contaminated site; Among them, 4-9g of iron-modified carbon composite material is required to purify 1L of groundwater from arsenic-contaminated sites; The iron-modified carbon composite material is ferrihydrite-modified carbon loaded with layered double metal hydroxides; The preparation method of the ferrihydrite-modified carbon-supported layered double metal hydroxide is as follows: S1. Dissolve Fe(NO3)3·9H2O in deionized water at a solid-liquid ratio of 1g:12~13mL, then add biochar accounting for 20~30% of the mass of Fe(NO3)3·9H2O, and stir at 250~350rpm for pre-adsorption for 23~25h; then adjust the pH to 7.15~7.25 with 0.8~1.2mol / L KOH solution, and stir at 350~450rpm for 12~14h; after stirring, centrifuge at 2900~3100rpm and retain the solid, then wash the solid with deionized water, centrifuge, freeze-dry, and grind through a 50~70 mesh sieve to obtain ferrihydrite-modified biochar; S2. Add 100 mL of water to 3-5 g of ferrihydrite-modified biochar, stir evenly, add 10 mL of 1 mol / L divalent metal salt, the metal is one of magnesium, nickel, and zinc; place the mixed solution in a reactor, react at 60°C-80°C for 20h-24h, centrifuge at 2900-3100 rpm to retain the solid, and wash the solid in deionized water for 3-5 times, then freeze-dry it and grind it through a 50-70 mesh sieve to obtain a composite material of ferrihydrite-modified carbon loaded with layered double metal hydroxides.

2. The method for purifying groundwater in an arsenic-contaminated site according to claim 1, characterized in that: The groundwater in the arsenic contaminated site contains coexisting ions, including SO4 2- 、HCO3 - 、CO3 2- PO4 3- At least one of .

3. The method for purifying groundwater in an arsenic-contaminated site according to claim 1, characterized in that: The biochar is prepared from fruit wood biochar by an oxygen exposure-spraying method, and is dried and ground through a 50-70 mesh sieve before use.

4. The method for purifying groundwater in an arsenic-contaminated site according to claim 3, characterized in that: The preparation method of the fruit wood biochar is as follows: solid alcohol is used as an igniter to ignite the precursor agricultural waste fruit wood branches, and oxygen is supplemented by the self-heating pressure difference generated by the combustion until the branches burn to black and red, and water is sprayed on the fruit wood branches in a spraying manner, and the water spraying volume is 50L / m 3 After the carbonized branches stop burning and cool down, the precursor is used to obtain fruit wood biochar.

Citation Information

Patent Citations

  • Method for treating arsenic-containing wastewater by using multiphase Fenton system based iron oxide

    CN106277278A

  • Preparation method and application of LDH modified biomass charcoal material

    CN114307944A